Prevalence of the Microsporidian Nosema spp. in Honey Bee Populations (Apis mellifera) in Some Ecological Regions of North Asia - Nadezhda V. Ostroverkhova; Olga L. Konusova; Aksana N. Kucher; Tatyana N. Kireeva; Svetlana A. Rosseykina (Veterinary Sciences, 2020)
Two species of microsporidia, Nosema apis and Nosema ceranae, are obligate intracellular parasites that are widespread in the world and cause the infectious disease (Nosemosis) of the Western honey bee Apis mellifera. Information on the prevalence and distribution of Nosema species in North Asia conditions is scarce. The main aim of the present study is to determine the prevalence of Nosema spp. (Nosemosis) in honey bees inhabiting some inland regions of North Asia (Western and Eastern Siberia, Altai Territory, Russia, and northeastern part of Kazakhstan). The objective of the paper is also to assess the influence of climatic factors on the spread of N. ceranae. Eighty apiaries in four ecological regions of North Asia (southern taiga, sub-taiga zone, forest steppe, and mountain taiga forests) were investigated with regard to distribution, prevalence, and diversity of Nosema infection in honey bees using duplex-PCR. Nosema infected bees were found in 65% apiaries of ecoregions studied, and coinfection was predominant (36.3% of Nosema-positive apiaries). Both N. apis and N. ceranae occur across subarctic and warm summer continental climates, but while N. apis predominates in the former, N. ceranae is more predominant in the latter. No statistically significant differences in Nosema distribution were identified in various climatic zones. In the sub-taiga zone (subarctic climate), low presence of colonies with pure N. ceranae and a significantly higher proportion of coinfection apiaries were revealed. Long-term epidemiological study of Nosema spp. prevalence in the sub-taiga zone showed a surprising percentage increase of Nosema-positive apiaries from 46.2% to 74.1% during 2012–2017. From 2012 to 2015, N. apis became a predominant species, but in 2016–2017, the coinfection was mainly detected. In conclusion, the results of this investigation showed that N. ceranae is widespread in all study ecoregions of North Asia where it exists in combination with the N. apis, but there is no replacement of N. apis by N. ceranae ...